A Prototype Gate-Drive Circuit for High-Voltage Inverter Adapting Simultaneously Inductive Wireless Transfer for Both Control Signal and Power - Ning Li; Haruto Yamamoto; Yuki Okada; Takeshi Shinkai (IEEE Access)
When driving an IGBT in a high-voltage inverter, the gate drive circuit requires high insulation for both the control signal and the power supply circuit. Non-integrated photo couplers are often used to isolate control signal circuits, and custom-made transformers for DC-DC converters are used to isolate power supply circuits. Because the floating gate drive circuit is located on the high-voltage side, the system with non-integrated photo couplers and custom-made transformers has low reliability and complexity, therefore, there is a high demand for robust and simple isolation methods. In this paper, a highly reliable and simple isolation method that utilizes simultaneous inductive wireless transfer for both the control signal and power is proposed, and the gate drive circuit is moved to the low-voltage side for high-voltage inverters used in large industrial motors and DC power transmission converters. Using the proposed method, it is easy to access the gate drive circuit and the insulation configuration becomes robust and simple compared with conventional systems. The effectiveness of this method is verified using a 40-V prototype three-phase inverter. A three-phase motor is successfully driven using the proposed prototype.